The kind of friends we used to be - Dowell, Frances O'Roark (Atheneum Books for Young Readers, 2010)
Twelve-year-olds Kate and Marylin, friends since preschool, draw further apart as Marylin becomes involved in student government and cheerleading, while Kate wants to play guitar and write songs, and both develop unlikely friendships with other girls and boys.